Tłumienie Układów Mechanicznych za Pomocą Cieczy Lepkosprężystych - Kamiński, E. (Engineering Transactions, 1973)
The paper presents the processes of damping by means of viscoelastic liquids. Equations of motion are found for the three-parameter Jeffreys liquid, and the effects of application of this liquid in three types of dampers arc demonstrated. Presented is also a new method of determination of parameters of a liquid model; the method, shown on the background of other methods, is based on the investigation of dynamic characteristics of a system with one degree of freedom.